Strategies Among Young Jehovah’s Witnesses in Compulsory School in Sweden, Age 13–15, a Case Study - Liedgren, Pernilla (International journal for the study of new religions, 2013)
This study investigated how young teenagers, as members of a strong religious organization, dealt with the school situation and the encounter with mainstream culture taking place at school during the final years in Swedish primary school (age 13-15 years). The purpose was to explore possible strategies that members of a minority group, in this case the Jehovah’s Witnesses, developed in order to deal with a value system differing from that of the group. We interviewed eleven former members of the Jehovah’s Witnesses about their final years in compulsory Swedish communal school. The ages of the interviewees ranged between 24 and 46 years, and the interviewed group comprised six men and five women. Nine of the eleven interviewees had grown up in the countryside or in villages. All but two were ethnic Swedes. The time that had passed since leaving the movement ranged from quite recently to 20 years ago. The results revealed three strategies; Standing up for Your Beliefs, Escaping, and Living in Two Worlds. The first two strategies are based on a One-World View, and the third strategy, Living in Two Worlds, implies a Two-World View, accepting to a certain extent both the Jehovah’s Witnesses outlook as well as that of ordinary society. The strategy Standing up for Your Beliefs can be described as straightforward, outspoken, and bold; the youngsters did not show any doubts about their belief. The second subgroup showed an unshakeable faith, but suffered psychological stress since their intentions to live according to their belief led to insecurity in terms of how to behave, and also left them quite isolated. These people reported more absence from school. The youngsters using the strategy Living in Two Worlds appeared to possess the ability to sympathize with both world views, and were more adaptable in different situations.